1989
DOI: 10.1111/j.1360-0443.1989.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Help‐seeking Behaviour in Problem Drinkers: a review

Abstract: Help-seeking behaviour in problem drinkers is still poorly understood. This paper summarizes the research conducted so far into alcohol related help-seeking, and attempts to integrate existing models of illness behaviours to help-seeking behaviour in problem drinkers. A conceptualization of alcohol related help-seeking behaviour is presented and empirical findings are reviewed. It was concluded that much of the research so far is exploratory in nature and the findings are still not easily related. Help-seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 25 publications
2
22
2
2
Order By: Relevance
“…Substance abusers themselves are the most direct source of information about the barriers that impede linkage with treatment, although their views have not always been considered (Jordan & Oei, 1989;Tsogia, Copello, & Orford, 2001). Exceptions include a large general population study where substance abusers identified their lack of confidence in the effectiveness of alcoholism treatment, stigmatization, and denial as conditions that would interfere with linkage (Grant, 1997).…”
Section: Substance Abusers' Perspectives Of Barriers To Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Substance abusers themselves are the most direct source of information about the barriers that impede linkage with treatment, although their views have not always been considered (Jordan & Oei, 1989;Tsogia, Copello, & Orford, 2001). Exceptions include a large general population study where substance abusers identified their lack of confidence in the effectiveness of alcoholism treatment, stigmatization, and denial as conditions that would interfere with linkage (Grant, 1997).…”
Section: Substance Abusers' Perspectives Of Barriers To Treatmentmentioning
confidence: 95%
“…Other antecedents, such as the number of arrests and prior treatment experiences, may also influence treatment entry. Unfortunately, very little is known about the interactive effect of obvious, but unchangeable, predisposing characteristics and subtle, yet changeable, barriers (Jordan & Oei, 1989). That may explain the reason why no one individual determinant has been consistently associated with treatment linkage (Hajema, Knibbe, & Droop, 1999;Hser et al, 1998;Kleinman, Millery, Scimeca, & Polissar, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Historically, most studies have operationalized treatment seeking as a dichotomous variable (i.e., according to whether or not treatment was obtained). These have been succeeded by studies that conceptualize treatment seeking as a process that comprises a series of decisions (Jordan & Oei, 1989, Mojtabai et al, 2002, Pringle, 1982, Saunders, 1993, Saunders, 1996, Simpson & Tucker, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Sur le plan de la reconnaissance du problème, les écrits révèlent que si le volume d'alcool ingurgité quotidiennement est souvent l'indice qui fait reconnaître l'existence d'un problème d'alcoolisme, la décision de demander de l'aide se présente généralement comme la résultante de plusieurs événements précipitants (problèmes relationnels, problèmes physiques, problèmes avec la loi) (Jordan et Oei, 1989). Si la peur d'avoir perdu le contrôle sur sa consommation peut être un facteur précipitant la demande d'aide chez les alcooliques (Brooke, Fudala et Johnson, 1992), c'est souvent à partir du moment où elle interfère dans la performance des rôles au travail ou au sein de la famille que la consommation est reconnue comme un problème (Thom, 1986).…”
Section: La Recherche D'aide Auprès Des Ressources Formelles : Quelquunclassified